Comprehensive characterisation of hypertensive heart disease left ventricular phenotypes. Issue 20 (3rd June 2016) - Rodrigues, Jonathan C L; Amadu, Antonio Matteo; Dastidar, Amardeep Ghosh; Szantho, Gergley V; Lyen, Stephen M; Godsave, Cattleya; Ratcliffe, Laura E K; Burchell, Amy E; Hart, Emma C; Hamilton, Mark C K; Nightingale, Angus K; Paton, Julian F R; et al.
Abstract : Objective: Myocardial intracellular/extracellular structure and aortic function were assessed among hypertensive left ventricular (LV) phenotypes using cardiovascular magnetic resonance (CMR). Methods: An observational study from consecutive tertiary hypertension clinic patients referred for CMR (1.5 T) was performed. Four LV phenotypes were defined: (1) normal with normal indexed LV mass (LVM) and LVM to volume ratio (M/V), (2) concentric remodelling with normal LVM but elevated M/V, (3) concentric LV hypertrophy (LVH) with elevated LVM but normal indexed end-diastolic volume (EDV) or (4) eccentric LVH with elevated LVM and EDV. Extracellular volume fraction was measured using T1-mapping. Circumferential strain was calculated by voxel-tracking. Aortic distensibility was derived from high-resolution aortic cines and contemporaneous blood pressure measurements. Results: 88 hypertensive patients (49±14 years, 57% men, systolic blood pressure (SBP): 167±30 mm Hg, diastolic blood pressure (DBP): 96±14 mm Hg) were compared with 29 age-matched/sex-matched controls (47±14 years, 59% men, SBP: 128±12 mm Hg, DBP: 79±10 mm Hg). LVH resulted from increased myocardial cell volume (eccentric LVH: 78±19 mL/m 2 vs concentric LVH: 73±15 mL/m 2 vs concentric remodelling: 55±9 mL/m 2, p<0.05, respectively) and interstitial fibrosis (eccentric LVH: 33±10 mL/m 2 vs concentric LVH: 30±10 mL/m 2 vs concentricremodelling: 19±2 mL/m 2, p<0.05, respectively). LVH had worst circumferential impairment (eccentric LVH: −12.8±4.6% vs concentric LVH: −15.5±3.1% vs concentric remodelling: –17.1±3.2%, p<0.05, respectively). Concentric remodelling was associated with reduced aortic distensibility, but not with large intracellular/interstitial expansion or myocardial dysfunction versus controls. Conclusions: Myocardial interstitial fibrosis varies across hypertensive LV phenotypes with functional consequences. Eccentric LVH has the most fibrosis and systolic impairment. Concentric remodelling is only associated with abnormal aortic function. Understanding these differences may help tailor future antihypertensive treatments.